Teenage girls fixing a meal outdoors - Unknown:::Creator::::::::::::
Photograph shows a group of teenage girls preparing a meal outdoors in a wooded area. They are standing around a table which has large pans and a large box on it. A food grinder is attached to the table on the far left corner. They are probably at the YWCA's Camp Ayun Mapu in Big Basin.